2024
DOI: 10.1039/d3nr06621e
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the assembly of nanoparticle organic hybrid materials (NOHMs) near an electrode interface with varying potential using neutron reflectivity

Md Ashraful Haque,
Sara T. Hamilton,
Tony G. Feric
et al.

Abstract: A critical concern regarding electrolyte formulation in an electrochemical environment is the impact of the interaction of the multiple components (i.e., supporting electrolyte or additive) with the electrode surface. Recently,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…31−34 The fundamental properties of NOHMs and their constituent polymers in electrolyte solutions have been extensively studied, 35−38 and they were found to mediate metal electrodeposition reactions at electrode interfaces, which are of interest in various electrochemical energy storage devices. 34,39 Because of the ability of polyethylenimine (PEI)-based NOHMs, as well as unbound PEI, to boost CO 2 concentration in solution, their potential to act as electrolyte additives for combined CO 2 capture and conversion has been investigated. 13,40 Feric et al recently demonstrated integrated capture and conversion of CO 2 in NOHMs and PEI-based electrolytes on a silver nanoparticle catalyst and found that their addition led to a change in selectivity and reaction rate compared to conventional aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31−34 The fundamental properties of NOHMs and their constituent polymers in electrolyte solutions have been extensively studied, 35−38 and they were found to mediate metal electrodeposition reactions at electrode interfaces, which are of interest in various electrochemical energy storage devices. 34,39 Because of the ability of polyethylenimine (PEI)-based NOHMs, as well as unbound PEI, to boost CO 2 concentration in solution, their potential to act as electrolyte additives for combined CO 2 capture and conversion has been investigated. 13,40 Feric et al recently demonstrated integrated capture and conversion of CO 2 in NOHMs and PEI-based electrolytes on a silver nanoparticle catalyst and found that their addition led to a change in selectivity and reaction rate compared to conventional aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric materials, such as nanoparticle organic hybrid materials (NOHMs), which consist of an organic polymeric canopy tethered to a nanoparticle core, are another class of CO 2 capture materials proposed for reactive capture. Due to their favorable properties, including negligible vapor pressure and high thermal stability under oxidizing conditions, , they have been proposed for CO 2 capture , and other electrochemical applications. The fundamental properties of NOHMs and their constituent polymers in electrolyte solutions have been extensively studied, and they were found to mediate metal electrodeposition reactions at electrode interfaces, which are of interest in various electrochemical energy storage devices. , Because of the ability of polyethylenimine (PEI)-based NOHMs, as well as unbound PEI, to boost CO 2 concentration in solution, their potential to act as electrolyte additives for combined CO 2 capture and conversion has been investigated. , Feric et al recently demonstrated integrated capture and conversion of CO 2 in NOHMs and PEI-based electrolytes on a silver nanoparticle catalyst and found that their addition led to a change in selectivity and reaction rate compared to conventional aqueous electrolytes …”
Section: Introductionmentioning
confidence: 99%